Profile Of Sexually Transmitted Diseases In A Clinic In The Suburb Of Kolkata (West Bengal) - Jaiswal A K; Chatterjee M; Walia N; Bal A S; Ramaswamy M S (Wolters Kluwer Medknow Publications, 2003)
Records of new STD patients attending the Base Hospital, Barrackpore, near Kolkata between 1991 and 2000 were analysed to examine the pattern of STDs among them. Among 567 new STD patients examined, syphilis predominated, followed by gonorrhoea, chancroid, genital warts, lymphogramuloma venereum and herpes genitalis. Non- gonococcal urethritis constituted 4.2% of study population. The overall HIV seropositivity showed a rising treads in the recent past.